Intentional marketing a practical guide for librarians - Ottolenghi, Carol (Practical guides for librarians, 2018)
"User-friendly, cost-conscious, and filled with examples from libraries of all types, Intentional Marketing: A Practical Guide for Librarians helps you maximize the return on your marketing investment (ROMI) by showing ways to combine marketing theory with in-house data, creating a global strategy that will drive all of your library marketing"--Provided by publisher.